Investigating the effects of therapist accuracy in cognitive behavioural therapy for depression. Issue 5 (3rd September 2018) - Antunes-Alves, Sara; Vukovic, Boris; Milyavskaya, Marina; Kramer, Ueli; Dobson, Keith; Drapeau, Martin
ABSTRACT: This study presents a means to address therapist accuracy in CBT as it relates to discussion of cognitive errors and coping strategies. Therapist interventions from CBT therapy sessions of 43 patients with depression were identified using the Comprehensive Psychotherapeutic Interventions Rating Scale, and focus of interventions on negative or positive cognitive errors, or affective, behavioural, or cognitive coping strategies was identified using the Cognitive Errors Rating Scale and Coping Patterns Rating Scale, respectively. Patients' depression symptoms were assessed using the Beck Depression Inventory. Prior to alpha adjustment, therapist accuracy of cognitive and behavioural coping strategies was found to significantly predict better coping. Tentative conclusions are provided on the value of attuning to patients' coping strategies.